A multi-section vertical absorption heat exchanger for district heating systems. (November 2016) - Zhu, Chaoyi; Xie, Xiaoyun; Jiang, Yi
Highlights: A novel multi-section absorption heat pump is developed for AHE in DH system. Performance of the entire multi-section AHE is tested in real project. The multi-section AHE was designed to realize large inlet/outlet temperature difference of external flow in each component. The new AHE has higher heat exchange effectiveness and better regulation performance. The simulation model for multi-section AHE is verified by the test data. Abstract: A novel building scale multi-section absorption heat exchanger (AHE) that is consist of a multi-section absorption heat pump and a plate heat exchanger was designed, developed and applied in district heating system to realize heat exchange from primary water to secondary water. The multi-section generating, condensing, absorbing and evaporating processes were designed to realize large external fluid inlet/outlet temperature difference in each component. The heat transfer loss can be reduced, and a low return primary water temperature can be reached to recover low grade waste heat as heat source. The performance of the prototype AHE was tested. The return primary water temperature was stable and was below 30 °C in the past two heating seasons, which was 10–15 K lower than inlet water temperature of secondary water. A temperature difference of 10 K–20 K in each component was realized. A pressure gradient from top to bottom was established to ensure stable fluid flow from top to bottom. The AHE has higher heat exchange effectiveness and better regulation performance compared with plate heat exchanger according to field test. And finally, the simulation model used to design the prototype machine was verified by the test results.